Soil macrofauna communities under plant cover in a no-till system in Thailand - Tantachasatid, Phakphoom; Boyer, Johnny; Thanisawanyankura, Sornprach; Séguy, Lucien; Sajjaphan, Kannika (Agriculture and Natural Resources, 2017)
The impact of no-till cropping systems with plant cover on soil macrofauna communities was assessed according to their abundance and biomass. The study was carried out in northeastern Thailand under a conventional cropping system (plow-based tillage), no-till cropping systems with plant cover (Brachiaria ruziziensis, Stylosanthes guianensis, S. guianensis associated with B. ruziziensis, rice straw) and under a natural dipterocarp forest. Soil macrofauna populations were sampled in 2007 (June and October) during the rainy season and at a beginning of the dry season, respectively. The results revealed that in the short term, the biological compartment responded quickly to the presence of plant cover, as shown by a significant increase in soil macrofauna abundance and total biomass. The highest mean total abundance (MTA) of 4224 individuals/m2 at the end of planting period (October 2007) was observed under S. guianensis cover and also the highest mean total soil macrofauna biomass (MTB) of 14.63 g/m2 was observed in the forest system in the same period. However, in the system of cultivation, the highest MTB of 11.33 g/m2 was observed under S. guianensis cover. Moreover, the change rate of soil macrofauna MTA was the highest under S. guianensis cover (+751.61%) and the change rate of soil macrofauna MTB revealed that this change rate was highest in forest (+430.07%). However, in the other systems of cultivation, the highest change rate of MTB was under S. guianensis cover (+12.96%).